2021
DOI: 10.1088/1748-0221/16/01/p01002
|View full text |Cite
|
Sign up to set email alerts
|

Radiation attenuation and photoluminescence properties of host tellurite glasses doped with Er3+ ions

Abstract: The application of shielding is one of the main protective measures in ionizing radiation safety. This paper addresses the influence of erbium oxide (Er 2 O 3 ) amount fraction on shielding properties of the glass system with compound formula 75TeO 2 -10Nb 2 O 5 -10ZnO-5PbO (TNZP). Addition of Er 2 O 3 portions increased samples densities from 5.57 to 5.65 g/cm 3 . The attenuation properties for the different TNZP-Er 2 O 3 samples were simulated using Phy-X/PSD software at vary wide energy ranged from 0.015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Transparent radiation shielding materials, as opposed to opaque radiation shielding materials, serve an essential role in nuclear engineering research because they provide substantial radiation protection while still being visible [1]. Recently, glasses have been considered as an alternative radiation shielding material due to properties such as their transparency, ease of manufacturing, nontoxicity, and high density [1][2][3][4][5][6][7][8]. Glass must be uniform in density and composition when used as a radiation shielding material.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent radiation shielding materials, as opposed to opaque radiation shielding materials, serve an essential role in nuclear engineering research because they provide substantial radiation protection while still being visible [1]. Recently, glasses have been considered as an alternative radiation shielding material due to properties such as their transparency, ease of manufacturing, nontoxicity, and high density [1][2][3][4][5][6][7][8]. Glass must be uniform in density and composition when used as a radiation shielding material.…”
Section: Introductionmentioning
confidence: 99%
“…Various conventional concretes (barite, chromite, ferrite, and magnetite) and available commercial glasses (RS-520, RS-360 and RS-253) utilized for radiation shielding materials were compared for HVL values against the S 5 sample (36). As demonstrated in Figure 6, the HVL values of S 5 oxide glass and these concretes had the same energy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the dramatic increase in the use of radiation in medical and industrial applications, radiation shielding issues have become an important topic among researchers [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted to study the effectiveness of glass as a radiation shield [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. All results concluded that glass could offer excellent shielding against radiation for different applications, such as nuclear power plants, agricultural machinery, industrial processes, and medical applications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%